2020
DOI: 10.3390/insects11040218
|View full text |Cite
|
Sign up to set email alerts
|

Biological Features and Population Growth of Two Southeastern European Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae) Strains

Abstract: A study of the biological features and the potential population growth between two laboratory strains of the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae) from Greece and Serbia is conducted on cracked barley and cracked white rice. The results show that, at a species level, T. confusum is able to complete development on cracked barley but not on cracked white rice. Therefore, cracked white rice proves to be an unsuitable commodity for T. confusum. Larval development on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Under starved conditions, lifespans fell to 24 days (resistant Ph-10) and 21 days (susceptible FSS-II). These reductions are similar to non-resistant adults when fed on the unsuitable rice diet (Kavallieratos et al, 2020). Adult malathion-resistant Musca domestica when exposed to oxygen survived better than a susceptible strain and induced higher catalase levels (Rauf et al, 2008).…”
Section: Lifespan and Survival Of The Strains Exposed To Oxidative Stressorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Under starved conditions, lifespans fell to 24 days (resistant Ph-10) and 21 days (susceptible FSS-II). These reductions are similar to non-resistant adults when fed on the unsuitable rice diet (Kavallieratos et al, 2020). Adult malathion-resistant Musca domestica when exposed to oxygen survived better than a susceptible strain and induced higher catalase levels (Rauf et al, 2008).…”
Section: Lifespan and Survival Of The Strains Exposed To Oxidative Stressorsmentioning
confidence: 94%
“…Depending on the strain, larval growth rates were negatively correlated with longevity of the adults. Strains originating from grain stores were compared for adult longevity and mean survival times were found to vary from 120 to 170 days (Kavallieratos et al, 2020) when fed on cracked barley. When fed on unsuitable rice grain the longevity was drastically shortened.…”
Section: Lifespan and Survival Of The Strains Exposed To Oxidative Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ability to infest processed commodities, it is usually found in mills, bakeries, pet shops, and storage units [ 2 ]. Recently, Kavallieratos et al [ 5 ] reported that the larval and pupal development period is a complex phenomenon depending on the geographical origin of T. confusum and the type of infested commodity.…”
Section: Introductionmentioning
confidence: 99%
“…It infests 138 different commodities such as cereal seeds, flours, bran, oilseeds, spices, as well as a wide variety of dry plant materials (e.g., fruits, nuts, herbs, coffee) [ 34 ]. It is considered as one of the most important enemies of stored cereals and processed cereals in a wide spectrum of storage facilities (e.g., mills, bins, bakeries) [ 1 , 34 , 40 , 41 , 42 ]. The qualitative and quantitative degradation of stored products in places where T. confusum occurs is particularly important, taking into account the significant financial losses on the basis of an annual global scale [ 11 , 39 ].…”
Section: Introductionmentioning
confidence: 99%